Super Realism : A Critical Anthology - Battcock, Gregory; Chase, Linda; Dyckes, William; Henry, Gerrit; Karp, Ivan; Levin, Kim; Marandel, J. Patric; Masheck, Joseph; Nemser, Cindy; Nochlin, Linda; Raymond, H. D.; Rosenberg, Harold; et al. (New York : E.P. Dutton & Co, Inc., 1975)
Alling, Janet ; de Andrea, John ; Artschwager, Richard ; Baeder, John ; Beal, Jack ; Bechtle, Robert ; Beckman, William ; Bell, Charles ; Besser, Arne ; Blackwell, Tom ; Bohnen, Blythe ; Bond, Douglas ; Clem Clarke, John ; Close, Chuck ; Cottingham, Robert ; Cross, Chris ; Woodburn, Stephen ; Cyrsky, Frank ; Douke, Dan ; Duchamp, Marcel ; Economou, Michael ; Eddy, Don ; Estes, Richard ; Everett, Bruce ; Fish, Janet ; Flack, Audrey ; Gertsch, Franz ; Goings, Ralph ; Gregor, Harold ; Haas, Richard ; Han, H.N. ; Hanson, Duane ; Hendricks, Donald T. ; Hoffman, Martin ; Hornak, Ian ; Jacquet, Alain ; Jacquette, Yvonne ; Jimenez, Luis ; Johnson, Guy ; Joseph, Richard ; Kacere, John ; Kanovitz, Howard ; Kessler, Alan ; Kleemann, Ron ; Kurt, Kay ; Leslie, Alfred ; Levine, Marilyn ; Ligare, David ; Mahaffey, Noël ; Mandel, John ; Plimack Mangold, Sylvia ; Mau, Michael ; McLean, Richard ; Mendenhall, Jack ; Midgette, Williard F. ; Miller, Mariann ; Moore, John ; Morley, Malcolm ; Nakagawa ; Nesbitt, Lowell ; Ott, Jerry ; Pearlstein, Philip ; Pettibone, Shirley ; Posen, Stephen ; Raffael, Joseph ; Ramos, Mel ; Rehm, Celeste ; Rummelhoff, John ; Salt, John ; Sandler, Barbara ; Schenck, William ; Schock, Carolyn ; Schonzeit, Ben ; Semmel, Joan ; Siburney, Alex ; Sobieski, Jean ; Stevenson, Harold ; Strider, Marjorie ; Warhol, Andy ; Weber, Idelle ; Ximenez, Antonio ; Yoshimura, Fumio
Engels
boek